Supporting radiography clinical placements in Ireland during the COVID-19 pandemic: The practice educators perspective. Issue 2 (March 2023) - O'Connor, M.; Lunney, A.; Potocnik, J.; Kearney, D.; Grehan, J.
Abstract: Introduction: The COVID-19 pandemic has significantly impacted healthcare services and the clinical learning environment. Several studies have investigated radiography students' experiences of clinical placement during the pandemic; however, few have investigated the Clinical Practice Educator's (CPEs) perspective. CPEs play a pivotal role in supporting clinical education. Method: A qualitative study was conducted using a purposeful sample of twenty-two CPEs, each working in a different Irish hospital. Four semi-structured focus groups were used to gather data. To maintain reasonable homogeneity, CPEs who were new to the role (n = 8) were assigned a separate focus group from experienced CPEs (n = 14). Inductive thematic analysis was applied. Results: CPEs experienced role expansion, particularly in managerial and administrative aspects of the role. They described arranging COVID-19 vaccinations locally for radiography students and the complexities of student rostering during the pandemic. CPEs perceived the pandemic to have impacted students' emotional wellbeing with 'high anxiety levels' and 'loneliness' being reported. They also perceived issues with clinical readiness and the student transition to clinical practice. Many challenges were faced by CPEs including arranging clinical recovery time for numerous students when sites were already at full capacity, fewer learning opportunities due to decreased patient throughput and range of imaging examinations, social distancing constraints, resistance from staff to student placements, and a shortage of staff for student supervision. Flexibility, communication, and multi-level support helped CPEs to fulfil their role. Conclusion: The results provide insight into how CPEs supported radiography clinical placements during the pandemic and into the challenges faced by CPEs in their role. CPEs supported student placement through multi-level communication, teamwork, flexibility, and student advocacy. Implications for practice: This will aid understanding of the support mechanisms needed by CPEs to provide quality clinical placements.